Structural and magnetic characterization of BaTiO3–BaFe12O19 bilayer thin films: Interface effects on the magnetic properties of barium hexaferrite layer - Zandalazini, Carlos Ivan (2021)
We report the successful growth of BaFe12O19–BaTiO3 (BaM-BTO) bilayer thin films using pulsed laser deposition, considering different crystallographic textures; BTO on (0001)-BaM and BaM on (100)-BTO. Our study involved the bilayers, the individual ferrite and titanate films, and the targets used in their growth. Raman spectroscopy and X-Ray diffraction were used to examine the structure of BaM-BTO thin films, indicating that there is no formation of impurity phases. The morphological characterization was made by scanning electron microscopy, and the magnetic behaviour was studied using SQUID magnetometry. The spontaneous magnetization, magnetic anisotropy constant, and anisotropy field were determined simultaneously from the magnetic hysteresis loop. In addition, we also studied the influence of different annealing temperatures over the magnetic behaviour of bare BaM and covered with BTO thin film. This allows to discern between the different magnetization reversal processes in bilayer systems, indicating a strong correlation between the anisotropy field and the coercive field, and an unusual linear relation of the anisotropy constant with the spontaneous magnetization. Our results indicate a direct influence of the BTO on the magnetic properties of the BaM phase, which places these composite bilayers as excellent candidates for the development of multifunctional devices.